2021
DOI: 10.1109/tr.2019.2956690
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Evolution of Android App Vulnerabilities

Abstract: The Android ecosystem today is a growing universe of a few billion devices, hundreds of millions of users and millions of applications targeting a wide range of activities where sensitive information is collected and processed. Security of communication and privacy of data are thus of utmost importance in application development. Yet, regularly, there are reports of successful attacks targeting Android users. While some of those attacks exploit vulnerabilities in the Android OS, others directly concern applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 89 publications
(107 reference statements)
0
21
0
Order By: Relevance
“…Millions of applications are freely available for download by Android users. However, malware developers keep targeting the platform and trying to get their abusive applications into the Android ecosystem [28,32,44]. For example, 360 Security recently reported that over 500,000 new mobile malware variants targeting the Android platform were found in China in the first quarter of 2019 [65].…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Millions of applications are freely available for download by Android users. However, malware developers keep targeting the platform and trying to get their abusive applications into the Android ecosystem [28,32,44]. For example, 360 Security recently reported that over 500,000 new mobile malware variants targeting the Android platform were found in China in the first quarter of 2019 [65].…”
Section: Motivationmentioning
confidence: 99%
“…Also, as of early 2020, 1 out of every 1000 app installs from Google's official Play store is from a potentially harmful application, as shown in the recent Google Transparency Report. 1 These numbers demand practical and scalable approaches and tools to support security analysis of large sets of Android apps [28,32,54].…”
Section: Motivationmentioning
confidence: 99%
“…In [13], we explained how we re-construct the versioned lineages of Android apps, by leveraging AndroZoo [5], a popular Android application repository made available to researchers. Then, we performed a large-scale investigation on how vulnerabilities evolve in Android apps.…”
Section: App Lineages To Perform Evolutionary Studiesmentioning
confidence: 99%
“…To perform this experiment, we consider app lineages (i.e., different versions of apps over time). To that end, we consider a large lineage dataset proposed by Gao et al [37] based on the AndroZoo repository. Most of the lineages are spread over several years, but for each year, we consider only the latest apk version in that year for a given lineage.…”
Section: Rq2: Evolution Of Dici Usagesmentioning
confidence: 99%
“…The statistics of apks per year from the lineage dataset in the literature is listed in Table 4. Table 4: # APKs considered from the Lineage dataset [37] 2011 2012 2013 2014 2015 2016 2017 2018 3,950 6,252 13,191 23924 17,505 30,690 6,995 3,583 We run DICIDer on this dataset and compute the percentage of apks containing DICIs for each year. The result is presented in Figure 6.…”
Section: Rq2: Evolution Of Dici Usagesmentioning
confidence: 99%